HEALTH COMMUNICATION LAW IN THE PANDEMIC CRISIS: AN EXAMINATION OF PUBLIC INFORMATION POLICY, GOVERNMENT ACCOUNTABILITY, AND IMPLICATIONS FOR THE PROTECTION OF PUBLIC RIGHTS - Hotmaria Hertawaty Sijabat; Andreas Harry; Gunawan Widjaja (ADISAM PUBLISHER, 2025)
This research discusses health communication law within the framework of the pandemic crisis with a focus on public information policy, government accountability, and implications for the protection of public rights. Transparent and accurate communication is a key element in delivering health information to the public to prevent misinformation and increase public awareness of pandemic mitigation measures. Government accountability in managing health communication policies also plays a major role in building public trust and ensuring effective policy implementation. In addition, this study highlights the importance of protecting people's rights, especially access to correct information and guaranteeing individual privacy, especially regarding health data. This study emphasises that health communication law should be a strategic instrument to balance crisis management with the protection of human rights and public communication ethics